ANALISIS PERAN GURU SEBAGAI AGEN PERUBAHAN DALAM PENDIDIKAN ABAD 21 - Mubarakah, Rumaisya Hanifah; Panjaitan, Theresia Nova Ishfihani; Ikmawati, Ikmawati; Untu, Zainuddin (Journal of Sustainable Transformation, 2025)
21st-century education demands changes in the role of teachers, who are not only educators but also agents of change in creating innovative and adaptive learning environments. This study aims to analyze the role of teachers in guiding students to develop 21st-century skills and the challenges they face in fulfilling this role. This research used a literature study by analyzing various relevant sources. The results showed that teachers face challenges such as gaps in technology mastery, limited training, and demands for innovation amid high workloads. To overcome these challenges, teachers need to improve their digital competencies, implement innovative learning strategies, and build collaboration. Technology-based learning, such as blended learning, project-based learning, and collaborative learning, has proven effective in improving education quality. With the right policy support, teachers can optimize their role as agents of change and contribute to a better education transformation.